2016
DOI: 10.1007/s00405-016-4007-4
|View full text |Cite
|
Sign up to set email alerts
|

What vestibular tests to choose in symptomatic patients after a cochlear implant? A systematic review and meta-analysis

Abstract: Vestibular function after cochlear implantation is difficult to understand, as subjective vestibular symptoms seem uncorrelated with the results of objective tests. Consequently, clinicians may struggle to decide what assessments to perform for a symptomatic patient. We used a systematic review and meta-analysis approach to enlighten this point. After a study inclusion process, results were classified into four different groups for each test in each study: (1) 'true positive' if the test showed impairment from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 69 publications
5
36
3
1
Order By: Relevance
“…Such differences are regardless of uni-or bilateral MD condition. However, our results for the VEMPs differ from those obtained in previous studies [24] wherein a disappearance and impairment of oVEMPs and cVEMPs after CI surgery has been reported. These authors suggest that some degree of damage occurs at the level of the utricle and saccule.…”
Section: Discussioncontrasting
confidence: 57%
“…Such differences are regardless of uni-or bilateral MD condition. However, our results for the VEMPs differ from those obtained in previous studies [24] wherein a disappearance and impairment of oVEMPs and cVEMPs after CI surgery has been reported. These authors suggest that some degree of damage occurs at the level of the utricle and saccule.…”
Section: Discussioncontrasting
confidence: 57%
“…Abouzayd et al revealed in a meta-analysis the poor sensitivity of a single vestibular test to explain subjective symptoms after cochlear implantation and recommend the implementation of more extensive perioperative vestibular diagnostics for cochlear implant candidates. 97 Nevertheless, further studies are needed to correlate subjective symptoms with respective impairments of vestibular receptors. We conducted a systematic review and meta-analysis of a larger population of studies to determine reliable data on postoperative vertigo and diagnostic results.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors [27, 28] reported that one-third of CI recipients complain of dizziness after surgery. A recent review aimed at determining the best test to evaluate vestibular function before and after CI surgery was published by Abouzayd et al, [29]. They found that the caloric test was least sensitive, VEMP results were most often impaired, and HIT results were generally conserved.…”
Section: Discussionmentioning
confidence: 99%